QUALITY CONTROL ANALYSIS OF LEATHER BAG PRODUCT USING SIX SIGMA METHOD AT CV CHIDEHAFU - Qibtya Salma; Ni Ketut Purnawati (Adisam Publisher, 2025)
The increasing competitiveness in the manufacturing industry drives companies to continuously improve efficiency and product quality to meet customer needs and expectations. In the leather-based craft industry, product quality becomes a key benchmark that directly influences marketability and customer loyalty. CV Chidehafu Denpasar, a producer of leather bags, faces challenges in reducing product defects that could impact production costs and brand image. Based on production documentation from January 2024 to April 2025, the defect rate was found to exceed the company's tolerance threshold of 1%. This study employs the Six Sigma method using the DMAIC (Define, Measure, Analyze, Improve, Control) approach to design a more effective quality control plan. The analysis reveals that out of 4,800 total units produced, 717 were defective, resulting in a DPMO value of 29,880 or equivalent to a 3.3 sigma level. The most common defects include dirty leather, scratched surfaces, and loose stitching. Through Pareto and FMEA analysis, several improvement actions were proposed, focusing on raw material handling and operator skill enhancement. The implementation of Six Sigma-based quality control is expected to significantly reduce product defects and enhance the overall efficiency and quality of leather bag production at CV Chidehafu Denpasar.